Management of undernutrition and failure to thrive in children with congenital heart disease in low- and middle-income countries. (4th December 2017) - Argent, Andrew C.; Balachandran, Rakhi; Vaidyanathan, Balu; Khan, Amina; Kumar, R. Krishna
Abstract: Poor growth with underweight for age, decreased length/height for age, and underweight-for-height are all relatively common in children with CHD. The underlying causes of this failure to thrive may be multifactorial, including innate growth potential, severity of cardiac disease, increased energy requirements, decreased nutritional intake, malabsorption, and poor utilisation of absorbed nutrition. These factors are particularly common and severe in low- and middle-income countries. Although nutrition should be carefully assessed in all patients, failure of growth is not a contraindication to surgical repair, and patients should receive surgical repair where indicated as soon as possible. Close attention should be paid to nutritional support – primarily enteral feeding, with particular use of breast milk in infancy – in the perioperative period and in the paediatric ICU. This nutritional support requires specific attention and allocation of resources, including appropriately skilled personnel. Thereafter, it is essential to monitor growth and development and to identify causes for failure to catch-up or grow appropriately.